Judicialization of medicines: effectiveness of rights or break in public policies? - Yonara Monique da Costa Oliveira; Bárbara Suellen Fonseca Braga; Andrezza Duarte Farias; Sylvia Patrícia Dantas Pereira; Maria Angela Fernandes Ferreira (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE: To analyze whether lawsuits for medicines filed against the state of Rio Grande do Norte agree with medical-sanitary and pharmaceutical assistance management criteria established by the public policies of access to medicines in force in Brazil. METHODS: This is a descriptive and retrospective study of the individual lawsuits that claimed medicines in the state of Rio Grande do Norte between 2013 and 2017. Information was collected from the procedural documents on the requested medicines, the diagnoses referred and the origin of the medical prescription, in order to analyze medical-sanitary and pharmaceutical assistance management characteristics. RESULTS: We analyzed 987 lawsuits, which requested 1,517 medications. Of these, 60.7% were not part of the National List of Essential Medicines, and, in 75% of the cases, there was a therapeutic alternative in the Brazilian Unified Health System. In 13.6% of the actions, at least one drug was prescribed for off-label use. Prescribers of philanthropic and private services often request medicines not covered by the pharmaceutical care policy. Even judicialized drugs that are part of the national list are constantly requested for non-standard indications. CONCLUSIONS: Court decisions for the supply of medicines violate health rules and make it difficult to manage pharmaceutical assistance, which may weaken the implementation of these policies.